Letrozole cotreatment with progestin-primed ovarian stimulation in women with polycystic ovary syndrome undergoing IVF treatment - Liu, Yali; Lin, Jiaying; Chen, Li; Mao, Xiaoyan; Wang, Li; Chen, Qiuju; Yu, Sha; Kuang, Yanping (Frontiers in Physiology, 2022)
Background: Progestin is an alternative to gonadotropin-releasing hormone (GnRH) analogues in the follicular phase to suppress the premature luteinizing hormone (LH) surge in women with polycystic ovary syndrome (PCOS). However, progestin-primed ovarian stimulation (PPOS) is always accompanied by increased pituitary suppression and gonadotropin consumption. Previous studies suggested that letrozole appeared to have the potential to reduce the total gonadotropin dose required for ovarian stimulation. A retrospective cohort study was performed to evaluate the efficacy of PPOS with or without letrozole in infertile women with PCOS. Methods: This retrospective cohort study included 448 women with PCOS who underwent controlled ovarian stimulation (COS) with human menopausal gonadotropin (hMG) and medroxyprogesterone acetate (MPA) (n=224) or hMG and MPA cotreatment with LE (n=224) from January 2018 to March 2021 after propensity-score matching. The primary outcome measure was the hMG dose. The secondary outcomes were the durations of ovarian stimulation, the implantation rate, the number of oocytes retrieved and viable embryos, oocyte maturity and fertilization rates, the percentage of women with profound pituitary suppression (luteinizing hormone [LH] <1.0 IU/L on the trigger day). Results: The hMG doses (1949.89±725.03 IU vs. 2017.41±653.32 IU, P>0.05) and durations of ovarian stimulation (9.03±1.79 days vs. 9.21±2.18 days, P>0.05) were similar between the two groups. The implantation rate was significantly higher in the study group (MPA+hMG+LE) than in the control group (MPA+hMG) (42.22% vs. 34.69%, P < 0.05). The numbers of oocytes and embryos retrieved were similar between the two groups. Interestingly, letrozole cotreatment was associated with decreased oocyte maturity and fertilization rates in comparison with standard PPOS protocols even though mature and fertilized oocyte yields were comparable. Compared with those in the control group, the LH values on the trigger day were significantly higher in the study group, together with significantly reduced pituitary suppression. Conclusion: Letrozole combined with PPOS cannot reduce hMG consumption in PCOS patients undergoing IVF treatment and shows no beneficial effect on cycle characteristics of COS. However, letrozole supplementation manifests as a superior implantation rate to that of the standard PPOS protocol in women with PCOS.